Utilization of Low Concentrations of Starch by a Flavobacterium Species Isolated from Tap Water - van der Kooij, D. (1981)
Experiments in well-cleaned glass flasks revealed that addition of starch in concentrations of 10 and 25 μg of substrate C per liter to the filtrate of slow sand filters stimulated the development of a yellow-pigmented bacterium which was identified as a Flavobacterium species. The isolate was able to multiply in tap water without substrates added, but addition of starch and glucose in amounts as low as 1 μg of substrate C per liter clearly enhanced growth. The substrate affinities of the Flavobacterium for these compounds were 3.9 μg of starch C and 3.3 μg of glucose C per liter. The results of this study indicate that microorganisms which rapidly utilize starch at a level of a few micrograms per liter commonly occur in water.